PENGARUH PENGGUNAAN LABA DAN ARUS KAS TERHADAP KONDISI FINANCIAL DISTRESS (Studi Pada Perusahaan Pertambangan Batu Bara Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2012-2014) - Novita Sari Dewi Nandrayani; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
This study aimed to examine the effect of the use of profit and cash flow to financial distress at a coal mining company listed on the Indonesia Stock Exchange year period 2012-2014. The population in this study are all coal mining companies listed on the Indonesia Stock Exchange year period 2012-2014. The sample in this study using purposive sampling method amounted to 19 companies. Data analysis techniques used in this study is the logistic regression analysis. Sources of data in this study were obtained annual financial statements published by the official website of the Indonesia Stock Exchange.  The results of this study showed that the profit and cash flow variables influence simultaneously toward financial distress. Meanwhile, the study also showed that the variable profit is partially affected the financial distress. And variable cash flows is partially affected the financial distress.